The effect of peer gender on major choice - Ulf Zölitz; Jan Feld (University of Zurich, Department of Economics, 2017)
This paper investigates how the peer gender composition in university affects students' major choices and labor market outcomes. Women who are randomly assigned to more female peers become less likely to choose male-dominated majors, they end up in jobs where they work fewer hours and their wage grows at a slower rate. Men become more likely to choose male-dominated majors after having had more female peers, although their labor market outcomes are not affected. Our results suggest that the increasing female university enrolment over recent decades has paradoxically contributed to the occupational segregation among university graduates that persists in today's labor market.
Keywords: I21; I24; J24; 330; Peer effects; major choice; gender composition